Non-specific, time-dependent desensitization of the vas deferens and anococcygeus preparations of the rat to alpha 1-adrenoceptor antagonists and atropine. - Onnen, I. (Nature Publishing Group, 1984)
Rat vas deferens preparations became desensitized to the alpha 1-adrenoceptor antagonist thymoxamine: after 6 h in vitro, the t 1/2 value (time to attain half the occupancy of receptors occupied at equilibrium) of the response to this drug was 1.50 fold greater in control strips (strips exposed to thymoxamine at 6 h) than in test strips (strips exposed to thymoxamine at 1 h). The rate of action of the alpha 1-adrenoceptor antagonist AR-C239 on the rat anococcygeus preparation was correlated with the rate of action of atropine. There was also a significant correlation between the t 1/2 ratios (1.37 and 1.30 for AR-C239 and atropine respectively) observed in the control muscles at 6 h. The in vitro slowing is thus due to some change in the longitudinal muscle and not to a change in the receptors. The in vitro slowing occurred when either phenylephrine or methoxamine was the alpha 1-adrenoceptor agonist used. The most likely mechanism of desensitization is a non-specific slowing of the access of drugs to receptors.